An approach for pre-runtime scheduling in embedded hard real-time systems with power constraints - Tavares, E.; Barreto, R.; O. Junior, M.; Maciel, P.; Neves, M.; Lima, R. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2004: Anais do XVI Symposium on Computer Architecture and High Performance Computing, 2004)
Embedded hard real-time systems have stringent timing constraints that must be satisfied for the correct functioning of the system. Hence all tasks must be finished before their deadlines. In addition, there are systems where energy is another constraint that must also be satisfied. In this paper, a pre-runtime scheduling algorithm is presented in order to find schedules satisfying both timing and energy constraints. The proposed approach uses state space exploration for finding pre-runtime schedules. However, the main problem with such methods is the space size, which can exponentially grow. This paper tackles this problem through a depth-first search method for generating a partial timed labeled transition system derived from the time Petri net model.